Investigation of the Relationship Between Location and Success in Venture Capital Investments: European Context - Breilh Ana Milena Montesdeoca; Dvouletý Ondřej (Studia Universitatis Vasile Goldis Arad, Seria Stiinte Economice)
Many academic studies explore the relationship between location and the likelihood of a successful outcome of venture capital investments. However, most of these studies are based in the United States. Nevertheless, the existing literature yielded contradicting findings. Some authors claim that the distance between venture capital and startup is crucial in explaining the latter’s venture success. Others find that this is not necessarily the case. This article aims to contribute to the topic by investigating this relationship within the European continent, particularly the countries of Germany, Switzerland, Austria and The Netherlands. The empirical results from the logistic regression estimated using data from Crunchbase covering years 2007-2021, suggest that location’s impact on the startup’s probability of success is negligible. This could mean that the ‘right’ business opportunity can attract investors, despite the geographical distance. The article contributes to the ongoing scholarly debate by providing recommendations for European policymakers.